2020
DOI: 10.31000/almaal.v2i1.2592
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Strategi Pengelolaan Wakaf Uang di Indonesia (Pendekatan Metode Delphi)

Abstract: Potential cash waqf in Indonesia is enormous. However, the fact that management of waqf money is still encountering many obstacles. This study tried to identify priority constraints become a bottleneck in the management of cash waqf in Indonesia, following the priority solution that can be offered in support of the management of cash waqf in Indonesia with the approach of the Delphi method. Delphi method is a systematic method of collecting opinions from a group of expert withdrawal through a series of questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Sehingga wakaf diberikan peran yang siginifikan dikalangan masyarakat ekonomi syari'ah dalam pengelolaan Lembaga dan mengatasi persoalanpersoalan wakaf yang ada (Hasanah et al, 2020;Nugroho, 2021;Nurjamil & Nurhayati, 2021;Putra, 2021;Tanjung et al, 2020).…”
Section: A Pendahuluanunclassified
“…Sehingga wakaf diberikan peran yang siginifikan dikalangan masyarakat ekonomi syari'ah dalam pengelolaan Lembaga dan mengatasi persoalanpersoalan wakaf yang ada (Hasanah et al, 2020;Nugroho, 2021;Nurjamil & Nurhayati, 2021;Putra, 2021;Tanjung et al, 2020).…”
Section: A Pendahuluanunclassified
“…Based on data from the Directorate of Waqf Empowerment of the Ministry of Religious Affairs in March 2016, the total waqf land reached 435,944,317 hectares. Until 2018, the Ministry of Agrarian and Spatial Planning / National Defense Agency (ATR / BPN) revealed that there were as many as 460 thousand hectares of waqf land owned by waqf institutions that were not used and became passive assets (Tanjung et al, 2020). In addition to the problem of many waqf assets, that are unproductive and only become passive assets.…”
Section: Introductionmentioning
confidence: 99%
“…However, this amount has not reached 1% of the potential waqf receipts. The main factor causing the low management of cash waqf is the lack of public literacy about waqf money (Tanjung et al, 2020). Some ways that can be done to increase waqf receipts are effective education and dissemination about waqf money, innovative waqf institution marketing strategies, and transparency and accountability of waqf institutions (Tanjung et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The main factor causing the low management of cash waqf is the lack of public literacy about waqf money (Tanjung et al, 2020). Some ways that can be done to increase waqf receipts are effective education and dissemination about waqf money, innovative waqf institution marketing strategies, and transparency and accountability of waqf institutions (Tanjung et al, 2020). Even though it is hoped that by channeling it to economic activities, productive SMEs will make recipients become givers in the future.…”
Section: Introductionmentioning
confidence: 99%